The effects of trade on national productivity - A stimulant or its handmaiden: An empirical evidence from ASEAN nations - Duong, Hoang Long (CTU Journal of Innovation and Sustainable Development, 2024)
The paper investigates the mediating relationship between Trade and National Productivity, proxied by economic growth rate in ASEAN from 2012 – 2021. Using data from the ASEAN Statistical Yearbook, this research, first, reinvigorates the positive effects of trade balance on national productivity to improve the international trade literature given new settings and contemporary contexts, second, examines the translating/mediating effects of trade towards economic performance in the ASEAN by a novel approach through the adoption of generalized least squares and structural equation models. Findings show that there is a positive correlation between FDI and economic growth, a negative between trade openness and economic growth. Interestingly, there is the mediating effects of trade towards the FDI-growth relationship, justified by the tremendous uplift after the presence of trade was conducted into the regression. Albeit found compatible, the paper constrains itself since it did not treat the confounding effects of local market characteristics such as governance structures, institutional quality, intervention of fiscal policies, and the monetary circulation as one of the internal factors; to which the present author humbly suggests for future studies. Moreover, because of data unavailability, hypotheses are tested over the 10-year span, which may impede the inference because of macroeconomic-level policy lags.